Market Access Approach to Urban Growth - Yoon Sang Moon (KDI Journal of Economic Policy, 2020)
This paper studies urban growth in Korean cities. First, I document that population growth patterns change over time and that the current population distribution supports random urban growth. I confirm two empirical laws—Zipf's law and Gibrat's law—both of which hold in the period of 1995-2015, but do not hold in the earlier period of 1975-1995. Second, I find a systematic employment growth pattern of Korean cities in spite of the random population growth. I examine market access effects on employment growth. Market access, a geographical advantage, has a significant influence on urban employment growth. The market access effect is higher in the Seoul metropolitan area than in the rest of the country. This effect is stronger on employment growth in the manufacturing industry compared to employment growth in the service industry. These results are robust with various checks (e.g., different definitions of urban areas). The results here suggest that policymakers should consider geographical characteristics when they make policy decisions with respect to regional development.
Keywords: R11; R12; J21; 330; Urban Growth; Market Access; Agglomeration Economies; City Size Distributions